2018
DOI: 10.1016/j.ccr.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and supramolecular chemistry of mono- and di-selenium analogues of metal dithiocarbamates

Abstract: This bibliographic review summarises the coordination chemistry of mono-and diselenium analogues of metal dithiocarbamate ligands, [RRꞌNCS2]-, as revealed by X-ray crystallography and spectroscopy (77 Se NMR and infrared). The Se-ligands are usually chelating but, bridging modes, up to 4, are known. Reflecting the larger size, greater polarisability and presence of a polar-cap (-hole), selenium atoms are more likely to be 2 involved in secondary-bonding (chalcogen-bonding) than sulphur when a competition exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…It was in the context of a long-held interest in secondary bonding interactions and the supramolecular architectures they sustain [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] and in the aforementioned biological relevance of Se … O chalcogen bonding interactions that the present survey of Se … O interactions operating in crystals was undertaken. This review of the crystallographic literature serves to highlight the diverse nature of selenium atom environments, geometries, oxidation states and numbers and types of Se … O secondary bonding interactions formed by selenium and the wide variety of supramolecular architectures these chalcogen bonding interactions sustain.…”
Section: Introductionmentioning
confidence: 99%
“…It was in the context of a long-held interest in secondary bonding interactions and the supramolecular architectures they sustain [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] and in the aforementioned biological relevance of Se … O chalcogen bonding interactions that the present survey of Se … O interactions operating in crystals was undertaken. This review of the crystallographic literature serves to highlight the diverse nature of selenium atom environments, geometries, oxidation states and numbers and types of Se … O secondary bonding interactions formed by selenium and the wide variety of supramolecular architectures these chalcogen bonding interactions sustain.…”
Section: Introductionmentioning
confidence: 99%
“…This falls off to 16% for bismuth to 10% for tellurium and then 6% (arsenic) and 5% (tin and antimony). One reason for the low adoption rates relates to the observation that secondary bonding interactions are extremely sensitive to steric hindrance-bulky groups present on the organometal center and/or ligands bound to the metal can preclude the formation of secondary bonding interactions [15][16][17][18][19][20][21][22][23]; steric considerations have been exploited for the rational design of coordination polymers in zinc and cadmium dithiolate chemistry [74]. However, in a recent commentary on supramolecular association involving metal centers, it was concluded that the energies of stabilization provided by various secondary bonding interactions was in the same range and often exceeded the energy of stabilization provided by conventional hydrogen bonding interactions [77].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…In continuation of a long-held interest of the supramolecular association in crystals mediated by secondary-bonding and related interactions involving the main group elements [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51], the present survey focuses upon the delineation of the supramolecular architectures featuring Se … N interactions in the crystals of mononuclear selenium molecules which operate in the absence of other obvious supramolecular synthons, such as hydrogen-bonding. This survey reveals a full range of zero-, one-, two-and three-dimensional architectures featuring Se … N interactions.…”
Section: Introductionmentioning
confidence: 99%